Exploring mental well-being, the emotional impact of visual impairment and experiences of prejudice and discrimination among adults from minority ethnic communities in the UK - Heinze, Nikki; Castle, Claire L. (Frontiers in Public Health, 2023)
Individuals with visual impairment (V.I.) may be disadvantaged in various aspects of their lives, including access to services and both clinical and non-clinical outcomes. For instance, V.I. has been associated with an increased risk of discrimination and poorer mental health, particularly where V.I. is acquired. People who lose their sight may experience stages of grief, including denial and acceptance, which have been linked to depression and well-being. Despite the public health implications of sight loss, and associated mental health challenges, explorations of the interrelated factors impacting on people with V.I. remains limited. This includes considerations of minority ethnic communities (MEC), who might experience prejudice and discrimination due to both ethnicity and disability. This secondary analysis of survey data provides preliminary insights into the emotional impact of V.I., mental well-being, and perceived prejudice and discrimination among MEC adults, including Asian and black adults. Findings highlight the need to explore the experiences of individual communities to identify variable support needs, with implications for services and community-based interventions. The study will be of interest to a readership from various public and mental health contexts, and offers representation of communities which have been underrepresented in V.I. research.